2022
DOI: 10.1016/j.jand.2021.11.003
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of Pediatric Overweight and Obesity: Position of the Academy of Nutrition and Dietetics Based on an Umbrella Review of Systematic Reviews

Abstract: This Academy of Nutrition and Dietetics Position Paper reports current evidence on pediatric overweight and obesity prevention interventions and discusses implications for registered dietitian nutritionists (RDNs). An overview of current systematic reviews provided evidence-based results from a range of nutrition interventions according to developmental age group (ages 2 to 5, 6 to 12, and 13 to 17 years). Twenty-one current systematic reviews of nutrition interventions demonstrated a beneficial effect of nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…In accordance with previous similar overviews, the participation of the community, parents, and school was an enabler for the intervention [ 12 ]. Our analysis similarly identified the importance of school-based interventions composed of PA and nutrition/diet.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In accordance with previous similar overviews, the participation of the community, parents, and school was an enabler for the intervention [ 12 ]. Our analysis similarly identified the importance of school-based interventions composed of PA and nutrition/diet.…”
Section: Discussionsupporting
confidence: 83%
“…A high volume of evidence related to children and adolescents had been identified in recent years and could represent an obstacle for decision makers [ 11 ]. Previous studies have suggested school-based interventions for the prevention of this condition [ 12 , 13 ], and they identified that most common treatments involved lifestyle interventions (i.e., regulated screen time for children) [ 14 , 15 ]. Additionally, it was reported that interventions (diet, family behavior, PA promotion, supervised exercise, lifestyle, or multicomponent interventions) were associated with a reduction in BMI [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous literature in other pediatric obesity interventions that demonstrated positive health-related benefits of individualized approaches. 65,66 Further, it is important for these interventions to provide consistent nutritional information and remain up to date with recommendations when providing information to families; stakeholders in the needs assessment noted that families often hear conflicting information regarding nutrition and feeding. With feeding and nutrition guidelines constantly evolving and not always being consistent across providers and healthcare organizations, it may be difficult for families to determine which guidelines to follow, representing a systems-level barrier to healthy feeding and eating.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, schools should not allow inappropriate foods and beverages to be sold or marketed within the school environment (e.g., a ban of vending machines), while providing education about healthy eating patterns [17, 74]. Examples of such integrated prevention strategies are in place in different countries.…”
Section: Key Factors After Two Years Of Life Related To Obesity Riskmentioning
confidence: 99%